Beat the heat: Movements of a cold‐adapted ungulate during a record‐breaking heat wave - Aidan C. Sheppard; Emily Z. Hollik; Lee J. Hecker; Thomas S. Jung; Mark A. Edwards; Scott E. Nielsen (Ecosphere)
Abstract The frequency and severity of extreme weather events such as heat waves are increasing globally, revealing ecological responses that provide valuable insights toward the conservation of species in a changing climate. In this study, we utilized data from two populations of GPS‐collared female wood bison (Bison bison athabascae) in the boreal forest of northwestern Canada to investigate their movement behaviors in response to the 2021 Western North American Heat Wave. Using generalized additive mixed‐effect models and a model selection framework, we identified a behavioral temperature threshold for wood bison at 21°C. Above this threshold, movement rates decreased from ~100 m/h at 21°C to a low of ~25 m/h at 39°C (150% decrease; −9%/°C). Extreme heat also contributed to changes in diurnal movement patterns, reducing wood bison movement rates and shifting the timing of peak activity from midday to early morning. These findings highlight the behavioral adaptations of female wood bison and underscore the need to understand the behavioral and physiological responses of cold‐adapted mammals to extreme weather events. Subsequent effects of thermoregulatory behavior may impact individual fitness and population viability, particularly at high latitudes where cold‐adapted species are increasingly exposed to severe weather resulting from anthropogenic climate change.